Retrospective evaluation of acute hyperkalemia of unknown origin during general anesthesia in dogs. (March 2023) - Tisotti, Tainor; Sanchez, Andrea; Nickell, Jordan; Smith, Christopher K.; Hofmeister, Erik
Abstract: Objective: To report and characterize cases of acute hyperkalemia of unknown origin in dogs under anesthesia. Study design: Multicentric retrospective clinical study. Animals: Medical records of 19 client-owned dogs that developed acute hyperkalemia during anesthesia. Methods: Anesthetic records of dogs developing acute hyperkalemia from January 2015 to December 2022 were evaluated. Data collected included demographics, duration of anesthesia until the episode, electrolytes and blood gas measurements, electrocardiogram (ECG) abnormalities, drugs used as part of the anesthetic protocol, hyperkalemia treatment and outcome. Results: A total of 13 cases met the inclusion criteria with documented acute hyperkalemia with no apparent underlying cause during anesthesia. Dogs were [mean ± standard deviation (range)] 6.5 ± 5.0 (3–10) years old and weighed 18.0 ± 14.3 (5.1–40.0) kg. All dogs were administered dexmedetomidine and an opioid as part of the premedication. All dogs had inhalation anesthesia of >60 minutes' duration. The first clinical sign was bradycardia that was minimally responsive to anticholinergic administration and was often accompanied by moderate/severe hypotension. These signs were rapidly followed by ECG changes compatible with hyperkalemia and/or cardiac arrest. Rapid identification and treatment for hyperkalemia, with or without dexmedetomidine reversal, resulted in survival of 12 dogs and one fatality. Conclusions and clinical relevance: Unknown origin hyperkalemia is a life-threatening complication that can occur during general anesthesia. In healthy dogs, preanesthetic administration of dexmedetomidine in association with an opioid and followed by inhalation anesthesia of more than 1 hour duration may predispose to this complication. A sudden decrease in heart rate >90 minutes after dexmedetomidine administration, or ECG changes, may warrant measurement of blood potassium concentrations.